Role of communication technologies in broadacre agriculture in Australia: an empirical analysis using panel data - Salim, Ruhul; Mamum, S.; Hassan, K. (Blackwell Publishing Asia, 2015)
This paper examines the role of communication technologies (CTs) in Australian broadacre agricultural production using data over the period of 1990–2013. Allowing for cross-sectional independence in the data, the pooled mean group and augmented mean group techniques are applied to estimate dynamic relationships among variables. The empirical results demonstrate that CTs affect agricultural output positively in the long run. The estimated elasticity is 0.237. This result suggests that government policies that lift investment in telecommunication facilities are shown to contribute to an increase of output in Australia’s broadacre agriculture in the long run.